2000
DOI: 10.1053/jhep.2000.9408
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C-induced hepatic allograft injury is associated with a pretransplantation elevated viral replication rate

Abstract: Hepatitis C virus (HCV) allograft infection after liverEnd-stage liver disease associated with hepatitis C virus (HCV) infection is the leading indication for liver transplantation. 1 Although the recurrence of posttransplantation viremia is nearly universal, 2-4 the rate and extent of HCV-induced allograft injury is variable. 5 At present, mechanisms of injury and reliable predictors of aggressive allograft injury induced by HCV remain elusive.HCV is a positive-sense, single-strand RNA virus that presumably r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…If the suppressed T cell function promotes viral production and increases intrahepatic viral load (V L ), a larger number of HCV is released to circulating blood resulting in a higher serum titer (V B ). Our study and others 37 demonstrate that intrahepatic HCV loads, V L , are not different between immunosuppressed and immunocompetent patients. Alanine aminotransferase levels are positively correlated with the half-life of infected cell death.…”
Section: Discussionsupporting
confidence: 69%
“…If the suppressed T cell function promotes viral production and increases intrahepatic viral load (V L ), a larger number of HCV is released to circulating blood resulting in a higher serum titer (V B ). Our study and others 37 demonstrate that intrahepatic HCV loads, V L , are not different between immunosuppressed and immunocompetent patients. Alanine aminotransferase levels are positively correlated with the half-life of infected cell death.…”
Section: Discussionsupporting
confidence: 69%
“…High viremia of this magnitude can be observed, however, when HCVinfected patients are undergoing immune suppressive therapy after transplantation. [22][23][24] Histological analysis of the liver of an HCV-infected mouse showed that most human hepatocytes were infected. Despite careful electron microscopic analysis, no viral or subviral particles could be identified in human hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several variables have been associated with a more severe HCV disease recurrence after LT, such as a high pretransplantation viral load, old donor age, the presence of significant graft steatosis, and the administration of steroid boluses. 4,[7][8][9] It is important to state, however, that most studies are retrospective and that there is a lack of homogeneity in the definition of severe HCV recurrence after LT.…”
Section: H Epatitis C Virus (Hcv)-related Cirrhosis Is the Leading Inmentioning
confidence: 99%